ANALISIS PROSEDUR PEMBERIAN KREDIT KOPERASI: Studi pada Koperasi Rahastra Credit Union Bandung - Dai, Ratna Meisa; Suryanto, Suryanto; Novianti, Selvi (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
This study aims to analyze crediting procedures. The research method used in this research is the descriptive method to describe crediting activities conducted by Cooperative Rahastra Credit Union in Bandung. This research uses the qualitative approach. The data obtained by using the research instrument is through observation, in-depth interview and documentation study. The results of the study indicate that crediting procedures include credit administration, credit documentation, credit approval, and credit processing. Implementation of credit procedures undertaken by the Cooperative Rahastra Credit Union in Bandung has not been maximized because there is still one indicator of lending procedures that have not been met. Indicators that have not been met is the stage of credit documentation, that is when doing credit analysis not all prospective borrowers through the credit analysis phase. Cooperative Rahastra Credit Union still uses the element of subjectivity in assessing prospective borrowers. As a result of not applying this credit analysis resulted in the addition of bad credit. Keywords: procedure, lending, credit analysis, cooperative